Implicit Learning and Football Performance under Psychological Pressure: A Narrative Review - Pourreza, Amir; Mainer-Pardos, Elena; Nobari, Hadi (International Journal of Sport Studies for Health, 2024)
Objective: This review aims to explore the potential of implicit learning to enhance football performance under psychological pressure. The focus is on examining how implicit learning might mitigate the negative effects of pressure and improve the consistency and effectiveness of football skills during high-stakes situations. Materials and Methods: A systematic search strategy was employed to gather relevant research from databases such as SPORTDiscus, PsycINFO, PubMed, Google Scholar, and Web of Science. Keywords included "implicit learning," "motor skills," "football," "pressure performance," and "choking under pressure." The review considered peer-reviewed articles published in English, focusing on studies that investigated the relationship between implicit learning and football performance under pressure. Results: Implicit learning, characterized by the unconscious acquisition of skills through repeated practice, shows promise in enhancing football performance under pressure by promoting automaticity and reducing cognitive load. Studies have demonstrated that implicit learning can lead to more automatic and smoother motor skills, potentially making them less susceptible to disruption by pressure. Evidence from research on penalty kicks and other football-related tasks supports the effectiveness of implicit learning in high-pressure situations. Conclusion: The review highlights the potential of implicit learning to buffer the effects of psychological pressure in football, promoting resilience and adaptability in high-stakes scenarios. Further research is needed to optimize training methods for implicit learning and explore its application across different football skills and pressure conditions. Integrating implicit learning strategies into football training programs could equip athletes with the mental tools to perform at their peak under pressure.